The Effect of 40%, 45% and 50% Fly Ash Subtitution in Self-Compacting Concrete (SCC) on the Setting Time, Porosity, and Compressive Strength Parameters with Sulfuric Acid Resistance - Adnan, Fachrul Rozy; Adji Putra Abriantoro (Universitas Nusa Putra, 2025)
Concrete often faces significant challenges in aggressive environments, such as those with high sulfate concentrations. This study aims to evaluate the impact of fly ash substitution on the properties of self-compacting concrete (SCC). The use of fly ash as a supplementary cementitious material has been extensively researched to enhance concrete performance. Fly ash, a byproduct of coal combustion in power plants (PLTU), has considerable potential as a cement replacement in concrete mixtures. In this study, four variations of fly ash content were examined in SCC mixtures with substitution levels of 0%, 40%, 45%, and 50%. A total of 40 cylindrical specimens, each measuring 20x10 cm, were analyzed to assess the effects of fly ash on various performance parameters of SCC, after curing for 28 days and subsequent immersion in a 2% sulfuric acid solution for 21 days. The results indicate that the inclusion of fly ash significantly retards the setting time of SCC, particularly at the 50% substitution level, where the initial setting time increased by 171% and the final setting time by 108%. Additionally, flowability improved by 23%, porosity was reduced by up to 53%, and the compressive strength and acid resistance of SCC were enhanced by 81% compared to conventional SCC without fly ash. Overall, this study demonstrates that fly ash substitution in SCC not only improves flowability and reduces porosity but also significantly enhances the strength and durability of concrete in aggressive environments, making it an effective solution for the development of durable and high-performance concrete.